Implementasi Kurikulum Merdeka Paud di Sekolah Penggerak TK Mutiara Hati - Nasywa, Arwa Nabilah; Kusumawati, Dian; Yenny Yuanita; Yulia Nur Annisa; Dita Handayani (Motekar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
This study discusses the implementation of the Merdeka curriculum in early childhood education units against the background of curriculum changes in the co-19 pandemic which had an impact on students, causing a decrease in school participation and learning loss. The purpose of this study is to determine the implementation, supervision and supporting and inhibiting factors in the implementation of the Merdeka curriculum in early childhood education.   This research uses a qualitative approach with a descriptive analysis method which aims to describe the state of the field, describe and explain the social situation that occurs. The results of the study provide an overview of the implementation, supervision and there are supporting and inhibiting factors in the implementation of the Merdeka curriculum for early childhood education at the Mutiara Bandung Kindergarten driving school.  The implementation of the Merdeka curriculum simplifies the learning process for students and provides new nuances through project-based learning.